BITS 3423-Information technology security - Selamat, Siti Rahayu; Yusof, Robiah; Abdollah, Mohd Faizal; Bahaman, Nazrulazhar (Jawatankuasa Penerbitan FTMK, 2006)
The objectives of this module is to introduce student in preparing a secure computing environment by using secure software, hardware and network. The task will involve the managing setup process, PGP application, preventive tools,anti-virus and other security tools. These tools will help student in understanding and applying the computer and information security areas and processes. Each lab offers student many opportunities to get hands-on and build new security tools skills. The lab module also exposes students about the threats to their computing environment such as their information and network.